PERBEDAAN HASIL BELAJAR SISWA PADA MODEL PEMBELAJARAN KOOPERATIF TIPE CIRC DAN MODEL PEMBELAJARAN KONVENSIONAL - Niak, Yandry; Mataheru, Wilmintjie; Ngilawayan, Darma Andreas (Universitas Papua, 2018)
This study aims to see differences in student learning outcomes in the material system of two-variable linear equations using the CIRC type cooperative model and conventional learning models. This research is comparative research. The experimental class uses the CIRC type cooperative model using teaching materials and student worksheets and control classes using conventional models without teaching materials and student worksheets. The end of the meeting is a test of learning outcomes. The data obtained were then analyzed through: descriptive analysis, t-test statistics, and hypothesis testing. The results showed that there were differences in learning outcomes of Class X students of SMK Negeri 2 Ambon who were taught using cooperative integrated reading and composition cooperative learning model (CIRC) and conventional learning models on the material of two-variable linear equation systems.Â DOI:Â https://doi.org/10.30862/jhm.v1i2.1040